Students’ Perspectives on the Intensity of Lecturer Corrective Feedback and Its Impacts on Their Self-Confidence and Self-Expression in Learning English - Muhayyang, Maemuna; Novia, Lely; Nappu, Syamsiarna (Celebes Journal of Language Studies, 2025)
The purpose of this study is to obtain data regarding students' perceptions of the intensity of corrective feedback (CF) provided by lecturers and its influence on their self-confidence and self-expression abilities. To achieve the above objectives, a qualitative approach was used thru in-depth semi-structured interviews conducted with students from the English Language Education Study Program, Faculty of Languages and Literature, Makassar State University, who were taking English courses thru synchronous and asynchronous media. To analyze the data obtained, this study uses thematic analysis, which includes the stages of transcription, data reduction, coding, categorization, and the extraction of thematic meaning. The results of the research data analysis show that (1) students positively perceive the intensity of corrective feedback, which includes attention, duration, and frequency, differing between one lecturer and another because synchronous CF provides space for direct interaction and quick clarification, while asynchronous CF gives students the opportunity to reflect and correct errors independently; and (2) the intensity of CF has a positive impact on increasing students' self-confidence and self-expression in English, both orally and in writing, although feedback that is too frequent and delivered inappropriately can reduce motivation and cause anxiety. The results of this study conclude that a balance of intensity and approach in providing corrective feedback has a positive impact on the optimal linguistic and psychological development of students.